Outcomes of Prophylactic Epiglottic Petiole Suspension at the Time of Complete Laryngofissure. (October 2019) - Bergeron, Mathieu; de Alarcon, Alessandro; Hart, Catherine K.; Rutter, Michael J.
Objectives: To compare the clinical outcomes of patients with prophylactic petiole suspension (PPS) at the time of laryngofissure and patients without PPS. Study Design: Retrospective case series. Setting: Tertiary pediatric hospital from May 2003 to August 2017. Subjects and Methods: Patients included those undergoing airway reconstruction with complete laryngofissure. Patients in the study group had PPS at the time of laryngofissure, while control group patients did not. Results: Eighty-one patients underwent complete laryngofissure (22 study patients, 59 controls) at a median age of 4.8 years (interquartile range, 2.1-9.7). Patients in the control group were younger at the time of the surgery (3.7 vs 6.5 years, P = .04). Other demographic and clinical data, including subglottic stenosis (SGS) grades, were similar. For patients with SGS, 53.8% and 46.2% in the study group had a grade 1-2 and 3-4 SGS, respectively, as compared with 46.2% and 53.8% in the control group ( P = .65). Manifestations of petiole prolapse included failure of decannulation (8.6%), exercise intolerance (16.0%), and obstructive sleep apnea (11.1%). After 4 years of follow-up, 4.5% of the study group versus 27.1% of the control group had prolapse of the petiole ( P = .04). Petiole prolapsed affected >50% of patients with no PPS after 10 years of follow-up. Patients with petiole prolapse at the first surveillance microlaryngoscopy and bronchoscopy after stent removal had an odds ratio of 10.2 (95% CI, 1.1-94.8; P = .04) of becoming symptomatic. Conclusion: Patients with PPS had significantly fewer symptoms after complete laryngofissure as compared with patients without PPS. PPS should be considered when a complete laryngofissure is being performed during airway reconstruction.